Assessing the vulnerability of national food security to international food price shocks: A new index - Minot, Nicholas; Vos, Rob; Kim, Soonho; Park, Beyeong; Zaki, Sediqa; Mamboundou, Pierre (International Food Policy Research Institute, 2024)
Recent spikes in staple food prices resulting from the invasion of Ukraine have once again highlighted the difficulty faced by low-income countries that rely on imports for a substantial portion of their food supply. To better understand which countries are most affected by higher world food prices, we propose a food import vulnerability index (FIVI). One version of the index describes the vulnerability of each country to higher world prices for each of 15 major staple foods. Another version of the FIVI is a national index, aggregating across the 15 commodities. Both are based on three components, the caloric contribution of the commodity(ies) in the national diet, the dependence on imports, and the level of moderate and severe food insecurity in the country. The values of the FIVI are calculated for 2020, the most recent year for which data are available.